Community Development Financial Institution (CDFI) program evaluation: a luxury but not a necessity?. (2nd January 2023) - McCall, Jamie R.; Hoyman, Michele M.
ABSTRACT: Community development financial institutions (CDFIs) are an integral component of US community economic development policy. These organizations differ in structure and client base, but they all seek to promote sustainable and equitable growth at the local level. By injecting capital into under-served markets, CDFIs facilitate development that may not otherwise occur. Attempts to measure and evaluate CDFI performance have often yielded disparate results. A systematic review of the literature reveals that capacity constraints have resulted in CDFI evaluations with wide variance in scope and rigor. Making comparisons across these institutions is difficult because there are few standardized performance metrics that could inform evaluations. Major CDFI funders in the philanthropic and public sectors often have competing demands and do not consistently use evaluations to guide their decisions. To incrementally advance CDFI research and promote a more accurate understanding of their impact, we recommend a shift towards utilization-focused evaluations (UFEs).